2005
DOI: 10.1081/css-200056865
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Polycyclic Aromatic Hydrocarbons in Sewage Sludge‐Amended Soil

Abstract: The objective of this research was to estimate the content of polycyclic aromatic hydrocarbons (PAHs) in sandy soil fertilized with various doses of sewage sludge. The experiment consisted of six plots to which the following doses of sewage sludge were added: 30, 75, 150, 300, and 600 t/ha. Sixteen PAHs from the United States Environmental Protection Agency list were determined by means of a high-performance liquid chromatography (HPLC) with UV detection after preliminary ultrasonic extraction. Content of PAHs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In the sludge used in this experiment, the total PAHs content was 5713 µg kg −1 (±428 µg kg −1 ) ( Table I) and, as opposed to the soil, had a considerably high content of 3 and 6-ring PAHs. The introduction of sludge into the soil resulted in an increase of the PAH content therein Oleszczuk and Baran, 2005c). During the whole study period, continuous variations in the content of the compounds studies were observed (Figure 2a).…”
Section: Pahs In Soilmentioning
confidence: 96%
“…In the sludge used in this experiment, the total PAHs content was 5713 µg kg −1 (±428 µg kg −1 ) ( Table I) and, as opposed to the soil, had a considerably high content of 3 and 6-ring PAHs. The introduction of sludge into the soil resulted in an increase of the PAH content therein Oleszczuk and Baran, 2005c). During the whole study period, continuous variations in the content of the compounds studies were observed (Figure 2a).…”
Section: Pahs In Soilmentioning
confidence: 96%
“…Some are toxic, mutagenic, and carcinogenic to humans (Cerniglia 1993) and are known to persist in the environment. The presence of PAHs can be found in numerous elements within the natural environment (water, soil, sediments) (Baran et al 2002;Baran, Bielińska, and Oleszczuk 2004;Oleszczuk and Baran 2005a;Oleszczuk and Baran 2005b). However, it has been evaluated (Paterson and Mackay 1989) that the main PAH sink is the soil.…”
Section: Introductionmentioning
confidence: 95%
“…Polyaromatic hydrocarbons (PAHs) are listed as priority pollutants by the U.S. EPA (Keith and Telliard 1979;Oleszczuk and Baran 2005a). Some are toxic, mutagenic, and carcinogenic to humans (Cerniglia 1993) and are known to persist in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…PAH contamination can be considered serious when the evaluated total of these compounds in soils is greater than 1000 µg/kg d.m. [24].…”
Section: Resultsmentioning
confidence: 99%